Current status and some solutions for resource restoration of the abalone (Haliotis diversicolor) at Bach Long Vi National Marine Protected Area - Dong, Dao Minh; Huong, Tran Van; Toan, Luong Huu (Vietnam Journal of Marine Science and Technology, 2019)
Variously colored abalone (Haliotis diversicolor Reeve, 1864) is the one of 22 protected species by Bach Long Vi National Marine Protected Area. In 1987, the yield of abalone was 37 tons per year, but it was reduced to 5 tons per year in 1992 and before the year of 2013, the yield is less than 1 ton per year [3]. Acording to the survey in October, 1974 the density ranged from 1 to 4 individuals/500 m2, the average for the all of island is 1.25 individuals/500 m2, the current reserve of variously colored abalone is about 0.05 tons. Some of the major causes of abalone depletion include the use of destructive fishing practices such as mines, cyanides, asynchronous development of infrastructure, and sources of pollution... Some solutions to recover the source of profit from abalone such as: The management board of Bach Long Vi National Marine Protected Area and competent authorities have to strengthen communication activities to protect the natural environment, resources as well as to have strong sanctions to strictly handle the environmental pollution activities, illegal methods of fishing. There is a need of research plan to rehabilitate Sargassum and reproduce abalone to return to natural enviroment. To invest in scientific research, to build the facilities and equipments for the management board of Bach Long Vi National Marine Protected Areas should be paid attention.